(untitled) (Biological Sciences - PJSIR, 2008)
The fruits of Grewia asiatica were evaluated for the antiemetic activity in the experimental model dogs, whereas, acute oral toxicity test was carried out in mice and rats. Maximum oral dose of 200 mg/kg and 600 mg/kg of crude alcoholic extract was found non toxic in mice and rats. Oral dose of crude alcoholic extract (120 mg/kg body weight) caused antiemetic effect in dogs in 3 h and controlled emesis centrally induced by Apomorphine (0.044 mg/kg body weight). This activity of G. asiatica was comparable with standard commercial anti-emetic drugs like Maxolon (Metoclopramide) and Largactil tablets 10 mg (Chlorpromazine) of M/s. Aventis Pharma., Pakistan